CALCULATION AND OPTIMIZATION OF FORCE AND POWER ON AUTONOMOUS SURFACE VEHICLE (ASV) AS MEANS OF MARINE ACCIDENT RESCUE - Herlambang, Teguh; Nurhadi, Hendro (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2024)
The strategic regional position makes Indonesia a world transportation crossing route with various modes of transportation through Indonesian territory to reach other islands, countries, or even continents. For this reason, a solution is needed to reduce the number of fatalities and injuries due to ship accidents that may occur. By reducing the evacuation time to a minimum, it will be possible to minimize the number of casualties and injuries if the ship has an accident. Considering that, in terms of usability and benefits, the Autonomous Surface Vehicle (ASV) can be an alternative as a form of Search and Rescue (SAR) ship. Based on the results of the ASV Ship design that suits these needs, a force and power analysis was carried out in accordance with the applicable theory. Of the 2 designs with a monohull shape and with different hull variations, with the main dimensions of the ASV Sang Nagari (LH=4.55 m, LWL=4.348 m, B=1.272 m, D=0.804 m T=0.45 m) and ASV Sang Nadibumi (LH=4.55 m, LWL=4.311 m, B=1.352 m, D= 0.802 m, T=0.4 m) obtained a displacement of 1.063 tons and a resistance of 1 kN for ASV Sang Nagari and 1.202 tons and a resistance of 2.6 kN for ASV Sang Nadibumi at a standard speed of 10 knots. Based on the results of the force analysis, it is concluded that the two ASVs have 2 forces in static conditions, that is, weight force and upward lift force (FBouyant). Based on the results of the efficiency of ASV Sang Nagari has a higher efficiency of 0.002% with 56.422% than ASV Sang Nadibumi with 56.420%.. The ASV linear model made from linearization has the properties of a controllable and observable, so this model can be applied to navigation and control systems.